Introduction to mobile communications engineering - Hernando, José M. (Artech House mobile communications library., 1999)
Presents an introduction to mobile communications engineering with an emphasis on radio propagation and systems design. The text covers all kinds of mobile systems - PMR, PAMR, and cellular - complete with system descriptions, planning aspects, and practical engineering data, plus information about systems, such as GSM, DEC and TETRA. It also provides the reader with the practical knowledge needed to deal with problems related to coverage prediction, frequency assignment, EM compatibility and broadband system performance. The book serves as a resource of information on propagation for radio link design; centralized source of base station engineering data; and guide to design methodology for trunked radio networks. -- Provided by publisher.